ANALISIS KUALITAS LAYANAN MOBILE BANKING TERHADAP KEPUASAN PELANGGAN (Studi Pada Bank X Area Semarang) - Purnomo, Andreana Yulia; Dwiyanto, Bambang Munas (Diponegoro Journal of Management, 2017)
All activities nowadays are  based on technology include in banking industry. One of the innovations that made banks which associated with the development of technology is the use of mobile banking. The aim of this study is to analyze whether electronic service influence on customer satisfaction.The  sample  in  this  study  were  160  respondents  that had  used mobile banking, with non-probability samples with analytical method used is  multiple linier regression using SPSS 23.The results of this study showed that the five independent variables has a positive and significant to the dependent variables, realiability(0,217), responsiveness (0,264), Assurance (0,200), Empathy (0,204) and Tangibles (0,120) to customers satisfaction